INVESTIGATION OF POTENTIAL LANDSLIDES DUE TO LIQUEFACTION ON THE BALAROA ROAD SECTION USING THE LIMIT EQUILIBRIUM METHOD - Ramadhani, Sriyati; Martini; Labombang, Mastura; Yuniar, Shafira (Journal of Applied Engineering Science, 2021)
The earthquake that occured on September 28, 2018 in Palu city triggered liquefaction. Balaroa is one of the affected locations by liquefaction. The Balaroa area has several landslides including the road section which causes slopes to form. The purpose of this study is to identify the potential of landslides due to liquefaction on the Balaroa road section based on numerical modeling using the limit equalibrium method. This study was carried out on the Balaroa road section, which is geographically located in West Palu sub district, Palu City, Central of Sulawesi Province. The slope stability analysis models three locations that are prone to landslides using the limit equalibrium method assisted by Slide 7.0 program.The results show that the safety factor value of those three locations on the Balora road section using methods of Ordinary, Bishop and Janbu is FS<1, it indicates that the slope is in unsafe condition and prone to lanslides, therefore it needs to be taken into consideration by government